Medição de velocidade por ultrassom doppler para fluídos multifásicos - Sbardelotto, Guilherme (2014)
The industry of Oil and Gas is always searching to reduce costs and increase the productivity and it is in constant technological development in areas like extraction and processing of oil and derivatives, maintenance and equipment inspection, among other technical activities. Among the projects, it’s the development of control tools and R&D automation projects that are applicable mainly in areas related with quantification of parameters such as: output, volume fraction, water content in oil, by treating of multiphase flows, between others involved in oil exploration process, which are of paramount importance to maximize exploration quality. This project is characterized by the development of a generation module of ultrasound pulses encoded in VHDL (Very High Speed Integrated Circuit Hardware Description Language) through a FPGA (Field-programmable Gate Array). In the ultrasound signal it’s possible to choose several options that allow a better reading of the environment. This signal passes by a protection circuit and it’s sent to an acquisition module, where it’s processed in real time by a program made in LabVIEW. The LabVIEW code then shows, in graphics, informations like multiphase flow velocity. From this project, another PRH-10 fellows group may develop specific modules, or enhance features so that the idea becomes an applicable product in Oil and Gas industry.